Elasticity Characterization of Liver Cancers Using Shear Wave Ultrasound Elastography: Comparison Between Hepatocellular Carcinoma and Liver Metastasis. (November 2017) - Choong, Kah Lai; Wong, Yin How; Yeong, Chai Hong; Gnanasuntharam, Gnana Kumar; Goh, Khean Lee; Yoong, Boon Kong; Pongnapang, Napapong; Abdullah, Basri Johan Jeet
Purpose: This was a feasibility study of shear wave ultrasound elastography for characterization of liver tumors and to compare the tissue elasticity values of hepatocellular carcinoma (HCC), liver metastases, and normal liver tissues. Methods: Forty-one patients and 30 healthy volunteers were recruited and categorized into HCC, liver metastasis, and control groups based on their computed tomography and sonographic examinations. Elasticity values of different groups were compared statistically. Results: Mean (standard deviation) elasticity values for HCC, liver metastasis, and normal liver tissue were 51.45 (14.96), 49.89 (13.82), and 6.63 (1.65) kilopascal, respectively. Statistically significant differences were found between the elasticity values of HCC and liver metastasis with normal liver tissue. Based on the receiver operating characteristics analysis, 18.25 kilopascal may differentiate the malignant focal liver lesions from the normal liver tissue with both sensitivity and specificity of 100%. Conclusion: Shear wave ultrasound elastography may be able to differentiate HCC and liver metastasis from normal liver tissue based on the tissue elasticity values.